PERANCANGAN BRANDING DAN PROMOSI BRAND SPEAK UP - Jessica Sinarjo (TANRA: Jurnal Desain Komunikasi Visual Fakultas Seni dan Desain Universitas Negeri Makassar, 2021)
Speak Up is a streetwear-style clothing line and has the concept of courage to speak out. This product is still in the development stage and requires clear branding and promotion for its introduction and creating brand awareness as a new brand. This design is intended to solve the Speak Up problem through branding and promotion design. The data was collected through interviews and SWOT analysis, which was then analyzed using descriptive qualitative methods. This design begins with the creation of a clear identity for Speak Up, starting with the logo, packaging, required stationery and t-shirt designs that are in accordance with the concept of Speak Up. Promotion used for Speak Up through social media and other creative media. The World Changer is the big idea of Speak Up which will be applied to all media created.